Lead with confidence, move your project forward, manage conflicts. (Boston, 2014)
Whether you need a crash course or a brief refresher, each book in the series is a concise, practical primer that will help you brush up on a key management topic. Advice you can quickly read and apply, for ambitious professionals and aspiring executives--from the most trusted source in business.
Keywords: Business meetings,Cuộc họp kinh doanh